Implementasi Peraturan Bupati Pelalawan Nomor 24 tahun 2016: Studi Pemotongan Tunjangan Tambahan Penghasilan Pegawai Negeri Sipil di Badan Pengelolaan Keuangan dan Aset Daerah - RAMZALI, T. ROY (Badan Riset dan Inovasi Daerah Kabupaten Pelalawan, 2023)
This research aims to analyze the implementation of the Pelalawan Regent Regulation Number 24 of 2016 concerning the deduction of additional income allowances (TPP) for Civil Servants (PNS) in the Regional Financial and Asset Management Agency (BPKAD) of Pelalawan Regency. Evaluation indicators involve communication, resources, implementers' attitudes, and bureaucratic structure. The research method employed is a survey with the object of study being the BPKAD of Pelalawan Regency. The sample includes all PNS employees in BPKAD Pelalawan using a census technique. Primary data is obtained through questionnaires and interviews, while secondary data is collected through observation and documentation. Data analysis employs quantitative descriptive analysis using the Likert Scale. The research findings indicate that the implementation of Pelalawan Regent Regulation Number 24 of 2016 related to TPP deductions in BPKAD Pelalawan only reached a score of 3.2. This score suggests that the implementation has not met the expectations of the Pelalawan Regency Government. The most dominant inhibiting factor is the inconsistency in TPP deductions at BPKAD Pelalawan.